Tanggung Jawab Pemerintah Terhadap Keamanan Data Diri Warga Negara Indonesia - Nainggolan, Riska Putri Yesika; Tjiptabudy, Jantje; Matitaputty, Merlien Irene (CAPITAN: Constitutional Law & Administrative Law Review, 2025)
Personal data is a human right protected by the constitution. Protection of personal data of Indonesian citizens is still weak, causing an increase in many cases of data leaks that are exploited by irresponsible parties. Protection of personal data in Indonesia is still sectoral, based on the authority granted by regulations governing personal data. The absence of specific regulations governing the protection of personal data causes frequent data leaks. The Ministry of Communication and Information has the authority to maintain personal security in Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, which gives the Ministry of Communication and Information the authority to supervise the implementation of electronic systems and transactions. The government's responsibility has been regulated in Article 58 paragraph 1 of Law Number 27 of 2022 concerning Protection of Personal Data, which states that "The government plays a role in realizing the implementation of personal data protection in accordance with the provisions of the law." The forms of efforts made by the government regarding the protection of its citizens' personal data are in the form of increasing system security, conducting security supervision, providing security certification, security auditors, cooperation with the security industry and the government has the authority to require violators to inform the public or related parties of the violation. Additional types of administrative sanctions may include written warnings, temporary suspension of personal data processing activities, deletion or destruction of personal data, and/or financial fines.